Adherence to Guidelines: A National Audit of the Management of Acute upper Gastrointestinal Bleeding. The REASON Registry - Yidan Lu; Alan N Barkun; Myriam Martel (Canadian Journal of Gastroenterology and Hepatology)
OBJECTIVES: To assess process of care in nonvariceal upper gastrointestinal bleeding (NVUGIB) using a national cohort, and to identify predictors of adherence to ‘best practice’ standards.